2014
DOI: 10.1007/s10344-014-0869-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of gum-line recession as a reliable technique to age tigers

Abstract: Like other members of the Panthera genus, tigers are threatened throughout their range. Given their conservation status research focused on their population dynamics in the wild is needed, including population growth, lifespan, and breeding success, which requires reliable estimates of age. Current techniques to estimate age in tigers are either not reliable and/or difficult to apply in the field. Gum-line recession accurately estimates age for mountain lions, but has never been tested for tigers. The goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Age estimates using GLR have been shown to correlate well with age estimates obtained from cementum analyses in some felids (Laundré et al 2000, Fàbregas and Garcés‐Narro 2014, Hiller and Tyre 2014). However, for Canada lynx, we found that GLR was not an accurate method, nor did it correspond well with age estimates using cementum annuli.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Age estimates using GLR have been shown to correlate well with age estimates obtained from cementum analyses in some felids (Laundré et al 2000, Fàbregas and Garcés‐Narro 2014, Hiller and Tyre 2014). However, for Canada lynx, we found that GLR was not an accurate method, nor did it correspond well with age estimates using cementum annuli.…”
Section: Discussionmentioning
confidence: 68%
“…The latter was demonstrated by a weak predictive capacity even after the removal of kittens and yearlings. The poor correlation of GLR with age in Canada lynx, relative to other felids (Fàbregas and Garcés‐Narro 2014, Hiller and Tyre 2014), may stem from differences in diet among species, and therefore the degree of tooth wear (Galbany et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations